2015
DOI: 10.1063/1.4918911
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of cesium azide at pressures up to 30 GPa studied using in situ Raman spectroscopy

Abstract: Cesium azide has been studied by Raman spectroscopy at pressures up to %30 GPa at room temperature. The sequence of phase transitions to Phase III (at 0.5 GPa), Phase IV (at 4.3 GPa), and Phase V (at %19 GPa) has been observed in agreement with recent X-ray diffraction studies. Phase III has been found to adopt a monoclinic C2/m structure with two azide anions in nonequivalent positions, where one set of azide anions appears to be orientationally disordered according to the observed Raman spectra. The transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The broad peak around 635 cm –1 marked by a black solid point can be attributed to the IR-active bending mode of N 3 – . Due to the pressure-induced distortion of azide ions, the IR-active bending vibration mode of N 3 – around 640 cm –1 becomes Raman-active and can be observed in Raman measurements (e.g., NaN 3 and CsN 3 ) under high pressures. , The Raman spectrum indicates that the LiN 3 remains stable in the C 2/ m crystal structure, and the N 2 has occurred phase transitions to ε-N 2 , as reported at 41.1 GPa. Meanwhile, after laser heating, all the Raman modes that belong to LiN 3 disappear.…”
Section: Resultsmentioning
confidence: 56%
“…The broad peak around 635 cm –1 marked by a black solid point can be attributed to the IR-active bending mode of N 3 – . Due to the pressure-induced distortion of azide ions, the IR-active bending vibration mode of N 3 – around 640 cm –1 becomes Raman-active and can be observed in Raman measurements (e.g., NaN 3 and CsN 3 ) under high pressures. , The Raman spectrum indicates that the LiN 3 remains stable in the C 2/ m crystal structure, and the N 2 has occurred phase transitions to ε-N 2 , as reported at 41.1 GPa. Meanwhile, after laser heating, all the Raman modes that belong to LiN 3 disappear.…”
Section: Resultsmentioning
confidence: 56%
“…The vibrational mode at 642 cm –1 is attributed to the IR-active bending mode of N 3 – . Due to the pressure-induced distortion of the azide group, this IR-active bending vibration mode of N 3 – becomes Raman active and can be observed in azides under high pressure. , The Raman modes at 865, 1187, and 1839 cm –1 do not belong to any internal modes of N 3 – , so it can be suggested that they originate from a pressure-induced chemical transformation to new kinds of Na–N compounds instead of the structural transition (γ-NaN 3 to δ-NaN 3 ) reported by Zhu et al The hexagonal P 6/ m -NaN 3 has been predicted in compressed NaN 3 , which is a metallic phase without Raman-active modes according to the theoretical calculations. So our spectral observation of cold-compressed NaN 3 shows unique pressure-induced chemical transformation behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, CsN 3 was found to has a relatively low polymerization pressure compared with LiN 3 , NaN 3 , and KN 3 . Although amount of experimental and theoretical studies about CsN 3 have been carried out, several problems about CsN 3 under pressure are still unsolved: (1) A controversy was currently existed about the structure of phase IV between recent Raman and X-ray diffraction study. , (2) The pressure-induced evolution of T­(E g ) mode has been found to trigger structural phase transitions in the tetragonal KN 3 , RbN 3 , and TlN 3 ; ,, however, it was absent in recent high-pressure study of CsN 3 due to the limitation of measuring range . (3) The high-pressure behaviors of NNN bending vibrations of CsN 3 have not yet been conducted so far, which have been found to play a significant role for exploring the evolution of azide ions under pressure. , …”
Section: Introductionmentioning
confidence: 99%
“…(1) A controversy was currently existed about the structure of phase IV between recent Raman and X-ray diffraction study. 17,25 (2) The pressure-induced evolution of T(E g ) mode has been found to trigger structural phase transitions in the tetragonal KN 3 , RbN 3 , and TlN 3 ; 14,16,27 however, it was absent in recent high-pressure study of CsN 3 due to the limitation of measuring range. 25 (3) The high-pressure behaviors of NNN bending vibrations of CsN 3 have not yet been conducted so far, which have been found to play a significant role for exploring the evolution of azide ions under pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation